International Accounting Standards Harmonisation: The Case of Iran Privatisation - Roudaki, Jamal (Accounting Department,, 2007)
Accounting standards harmonisation literature shows that from the beginnhg of the twenty ï¬rst century IASs and IFRSs are receiving increasing attention from professional accounting bodies and stock market authorities of developed and developing countries more than ever before. Consequently number of countries chose to join the lAS users have incresed dramatically in recent years. The objective of this paper is to explore how Iranian Accounting Standards Board achieves harmonisation with IASs and lFRSs while govemment using some efforts to develop local stock market as means of privatisation. Tehran Stock Exchange which is involved in the third wave of country privatisation required companies to prepare their ï¬nancial reports using National Accounting Standards. These standards are in harmony with lASs and lFRs as they are developed based on the same procedure of lASBâ€™s â€œdue processâ€. In the same way, proposed projects of lran Accounting Standards Boards aim to develop conceptual framework in order toestablish a platform for standard setting. Due to recent development in privatisation in relation to internationally harmonised national accounting and auditing standards the standard setting in lran is in the state of ï¬‚ex national and international wise. Key words: International Standards Harmonisation, lntemational Accounting Standards, Privatisation and accounting standards, Iran Accounting Standards